2023
DOI: 10.3390/ijms24043345
|View full text |Cite
|
Sign up to set email alerts
|

CB2 Receptor as Emerging Anti-Inflammatory Target in Duchenne Muscular Dystrophy

Abstract: Duchenne Muscular Dystrophy (DMD) is a very severe X-linked dystrophinopathy. It is due to a mutation in the DMD gene and causes muscular degeneration in conjunction with several secondary co-morbidities, such cardiomyopathy and respiratory failure. DMD is characterized by a chronic inflammatory state, and corticosteroids represent the main therapy for these patients. To contradict drug-related side effects, there is need for novel and more safe therapeutic strategies. Macrophages are immune cells stringently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…anti-hyperalgesia in periphery. Such CB2-mediated anti-inflammatory effect has been observed in models of neuropathic and inflammatory pain[15], rheumatoid arthritis[16], multiple schlerosis[17], Duchenne Muscular Dystrophy[18] and even more[19]. Our previous study using CB2 knockout animals showed that lack of CB2 signaling exacerbates neuroinflammation[57], which supports anti-inflammatory role of CB2 receptors.…”
Section: Discussionsupporting
confidence: 60%
“…anti-hyperalgesia in periphery. Such CB2-mediated anti-inflammatory effect has been observed in models of neuropathic and inflammatory pain[15], rheumatoid arthritis[16], multiple schlerosis[17], Duchenne Muscular Dystrophy[18] and even more[19]. Our previous study using CB2 knockout animals showed that lack of CB2 signaling exacerbates neuroinflammation[57], which supports anti-inflammatory role of CB2 receptors.…”
Section: Discussionsupporting
confidence: 60%
“…In this respect, the pathogenesis of Duchenne Muscular Dystrophy (DMD), an X-linked dystrophinopathy due to a mutation in the DMS gene encoding for dystrophin, is characterized by muscular degeneration in conjunction with several secondary co-morbidities, such as cardiomyopathy, respiratory failure, and chronic inflammatory states [ 21 ]. Argenziano et al [ 22 ] analyzed the effect of the CB2 agonist JWH-133 on DMD-associated primary macrophages, revealing that the pharmacological activation of CB2 counteracts inflammation by inhibiting the release of pro-inflammatory cytokines and by directing the phenotype of macrophages toward anti-inflammatory and immunosuppressive activities (i.e., M2 status). Hence, the authors highlight the promising possibility to target CB2 in DMD as an additional and effective anti-inflammatory therapy.…”
mentioning
confidence: 99%